Optical properties and carrier dynamics in Co-doped ZnO nanorods. Issue 1 (18th November 2020) - K. Sivan, Aswathi; Galán-González, Alejandro; Di Mario, Lorenzo; Tappy, Nicolas; Hernández-Ferrer, Javier; Catone, Daniele; Turchini, Stefano; Benito, Ana M.; Maser, Wolfgang K.; Steinvall, Simon Escobar; Fontcuberta i Morral, Anna; Gallant, Andrew; et al.
Abstract : Optoelectronic and photoelectrochemical characterization of Co-doped ZnO nanorods revealing the crucial role of surface defects for enhanced photoresponse. Abstract : The controlled modification of the electronic properties of ZnO nanorods via transition metal doping is reported. A series of ZnO nanorods were synthesized by chemical bath growth with varying Co content from 0 to 20 atomic% in the growth solution. Optoelectronic behavior was probed using cathodoluminescence, time-resolved luminescence, transient absorbance spectroscopy, and the incident photon-to-current conversion efficiency (IPCE). Analysis indicates the crucial role of surface defects in determining the electronic behavior. Significantly, Co-doping extends the light absorption of the nanorods into the visible region, increases the surface defects, and shortens the non-radiative lifetimes, while leaving the radiative lifetime constant. Furthermore, for 1 atomic% Co-doping the IPCE of the ZnO nanorods is enhanced. These results demonstrate that doping can controllably tune the functional electronic properties of ZnO nanorods for applications.